ANALYSIS OF CASH FLOW STATEMENT TO ASSESS THE COMPANY'S FINANCIAL PERFORMANCE AT PT ASTRA INTERNATIONAL TBK. - Tri Yeni Suciani; Supanji Setyawan (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
Companies must keep track of their financial health and performance in order to meet their objectives. Financial statements are used to examine a company's financial performance. Analyzing cash flow figures can be used to evaluate a company's financial performance. This is a descriptive study that employs quantitative approaches. The data used is secondary data from PT Astra International Tbk's annual report in the form of cash flow reports. Cash flow ratio analysis was utilized as an analytical approach. The operating cash flow ratio, capital expenditure ratio, cash coverage ratio to current liabilities, cash coverage ratio to net income, and total debt ratio were all considered in this study. The findings of the cash flow ratio calculation indicate that PT Astra International Tbk. has a poor financial performance.